The critical role of boric acid as electrolyte additive on the electrochemical performance of lead-acid battery - Wu, Zhongfei; Liu, Yu; Deng, Chengzhi; Zhao, Haimin; Zhao, Ruirui; Chen, Hongyu (Journal of energy storage, 2020)
•Boric acid is used as electrolyte additive for lead-acid battery in the current research.•The working mechanism of the boric acid additive is studied thoroughly.•The boric acid can participate in the electrochemical reactions directly.•The battery with boric acid exhibit prolonged cycling performance due to the improved anti-corrosion properties. Electrolyte additives are essential for the performance enhancement of lead-acid batteries, which are paid lots of attention in recent years. Even boric acid has been reported as a helpful additive in lead-acid battery in previous papers, but the insufficient understanding concerning to the working mechanism still hinder its practical application. In this paper, the boric acid is used as an additive in lead-acid electrolyte, while electrochemical methods, scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectra are employed to study its critical effects on the battery performance. Results indicate that boric acid can increase both the hydrogen evolution overpotential and oxygen evolution overpotential of the lead grid due to the changed mean ionic activity coefficient of the solution, thus reducing the water loss during battery operation. The beneficial effects boric acid introduced possibly resulted from the formation of BO33−-contained products with dense morphology, which can hinder the further corrosion of the lead grids, results in prolonged battery life. [Display omitted]